2004
DOI: 10.1080/14017430310016180
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of color doppler tissue velocity imaging for assessment of regional timing of left ventricular longitudinal movement

Abstract: OBJECTIVE--The feasibility of color Doppler tissue velocity imaging (c-TVI) with a high time resolution of 10 ms for simultaneous measurement of the temporal characteristics of regional left ventricular (LV) tissue velocities at different LV sites was examined. Methods and results--In 20 subjects with structurally normal hearts, inter- and intraobserver agreement and the beat-to-beat variation were tested in c-TVI profiles from basal and mid-LV segments of the interventricular septum (IS) and of the lateral fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…10 SYS seems to be more affected by CRT, especially in the patients with a delayed LV free wall at baseline. Our finding that some patients had a counterintuitively delayed IVS, despite LBBB, points in the same direction as recently published studies showing that QRS duration and configuration do not predict the pattern of LV asynchrony in patients with bundle branch block.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…10 SYS seems to be more affected by CRT, especially in the patients with a delayed LV free wall at baseline. Our finding that some patients had a counterintuitively delayed IVS, despite LBBB, points in the same direction as recently published studies showing that QRS duration and configuration do not predict the pattern of LV asynchrony in patients with bundle branch block.…”
Section: Discussionmentioning
confidence: 90%
“…8 The systolic c-TVI peaks appear within 10 ms in structurally normal hearts. 10 The simultaneous velocity curves of four selected LV segments were compared for a mean of two consecutive beats. LV tissue velocities and peak tissue velocities were measured during IVC and SYS.…”
Section: Echocardiographic Methodsmentioning
confidence: 99%
“…Tissue Doppler imaging is today a well‐established method for the quantitative analysis of longitudinal myocardial velocity and deformation (Palmes et al. , 2000; Brodin, 2004; Schuster et al. , 2004), and it has been shown that disturbances in the myocardial function first occur in the longitudinal direction, partly compensated by an increased motion in the radial direction(Vinereanu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Tissue Doppler imaging is today a well-established method for the quantitative analysis of longitudinal myocardial velocity and deformation (Palmes et al, 2000;Brodin, 2004;Schuster et al, 2004), and it has been shown that disturbances in the myocardial function first occur in the longitudinal direction, partly compensated by an increased motion in the radial direction (Vinereanu et al, 2002(Vinereanu et al, , 2003Fang et al, 2004). Several studies have demonstrated the usefulness of myocardial longitudinal velocities to quantify regional left ventricular function in patients with various different heart diseases (Cain et al, 2001;Madler et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative tissue velocity imaging is a robust and reproducible echocardiographic tool based on tissue Doppler imaging with even higher spatial and temporal resolution, which permits quantitative assessment of both global and regional function and the timing of myocardial events 6 , 7 . In addition, quantitative tissue velocity imaging has the capacity to assess LV dysfunction as early as 1 day after onset and provide ventricular function information despite a high heart rate, which cannot be accomplished with conventional echocardiography 8 .…”
mentioning
confidence: 99%